Conversations about wellness and support in an aboriginal teacher education program - Legare, Louise Marie (2011)
Traditional Indigenous societies had intact ways of teaching, learning, and education. After contact with non-Indigenous peoples, educational orientations and practices which respect and reflect Aboriginal context, community, and culture were influenced and changed. In the present context, Métis and First Nations peoples in Canada have been in the process of reclaiming educational authority of their children and youth. One way that this educational authority has more recently been realized is through the establishment of Aboriginal Teacher Education Programs (ATEPs) where Aboriginal individuals are being prepared to be teachers for the teaching profession. Aboriginal TEPs are distinct entities within university teacher preparation programs. Aboriginal TEPs are unique in approach and functioning and reflect the ideological orientations and practices of the Aboriginal communities in which they are situated. This study explored the understandings of both Aboriginal and non-Aboriginal staff and faculty in relation to wellness and support within the Saskatchewan Urban Native Teacher Education Program (SUNTEP), in Prince Albert, Saskatchewan, Canada. This is a case study of one site. The findings provide a meaningful conception of the functions of wellness and support at the research site and were described from the participants primarily as relationships with self, family, and community.